"Queer temporality and refutation of linear time in "In the Waiting Room" & "Sestina" of Elizabeth Bishop with insights from the theory of Queer Time by Halberstam." - Mishaal Harb Mkhailef (مجلة الباحث, 2026)
This research will interpret the poetry of Elizabeth Bishop as resisting linear time in its structures, scenes, and affects for "In the Waiting Room" and "Sestina" to illustrate the truth of Jack Halberstam’s formulation of "queer time". According to Halberstam, “queer time” refers to an alternative to linear modes of temporal existence that structure subjectivity and world-building. It resists narratives of progress that move from childhood to adulthood and toward other developmental or normative endpoints. Through this analysis, I will argue for the existence of "queer time" within Bishop’s poetics as one of halted childhood perception and recursive time, where "In the Waiting Room" mediates temporal dislocation as an aftereffect of a moment of shock experienced by a child subject and "Sestina" codifies temporal dislocation as an effect of "queer time" typified by Jack Halberstam’s notion of "alternative chronologies".